Vacuum level dependent photoluminescence in chemical vapor deposition-grown monolayer MoS 2 - Sun, Linfeng (2018)
The stronger photoluminescence (PL) in chemical vapor deposition (CVD) grown monolayer MoS2 has been attributed to its high crystal quality compared with that in mechanically exfoliated (ME) crystal, which is contrary to the cognition that the ME crystal usually have better crystal quality than that of CVD grown one and it is expected with a better optical quality. In this report, the reason of abnormally strong PL spectra in CVD grown monolayer crystal is systematically investigated by studying the in-situ opto-electrical exploration at various environments for both of CVD and ME samples. High resolution transmission electron microscopy is used to investigate their crystal qualities. The stronger PL in CVD grown crystal is due to the high p-doping effect of adsorbates induced rebalance of exciton/trion emission. The first principle calculations are carried out to explore the interaction between adsorbates in ambient and defects sites in MoS2, which is consistent to the experimental phenomenon and further confirm our proposed mechanisms.